2013
DOI: 10.3748/wjg.v19.i6.802
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of adiponectin in obesity related non-alcoholic fatty liver disease?

Abstract: Non-alcoholic fatty liver disease (NAFLD) is recognized as the most common type of chronic liver disease in Western countries. Insulin resistance is a key factor in the pathogenesis of NAFLD, the latter being considered as the hepatic component of insulin resistance or obesity. Adiponectin is the most abundant adipose-specific adipokine. There is evidence that adiponectin decreases hepatic and systematic insulin resistance, and attenuates liver inflammation and fibrosis. Adiponectin generally predicts steatosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
131
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 139 publications
8
131
2
5
Order By: Relevance
“…Obesity may lead to an imbalanced production of pro-and antiinflammatory adipokines secreted from adipose tissue, which contributes to the pathogenesis of NAFLD. In particular a decreased release of adiponectin, an adipokine known to exert anti-inflammatory and insulin-sensitizing effects, has been found to play a crucial role in the pathogenesis of NAFLD [43,44]. Accordingly we found that HGI levels were positively associated with measures of visceral obesity such as BMI, waist circumference and % fat mass.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Obesity may lead to an imbalanced production of pro-and antiinflammatory adipokines secreted from adipose tissue, which contributes to the pathogenesis of NAFLD. In particular a decreased release of adiponectin, an adipokine known to exert anti-inflammatory and insulin-sensitizing effects, has been found to play a crucial role in the pathogenesis of NAFLD [43,44]. Accordingly we found that HGI levels were positively associated with measures of visceral obesity such as BMI, waist circumference and % fat mass.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, visceral obesity and the consequent adipose metabolic dysfunction represent important risk factors for the development and progression of NAFLD [43,44]. Obesity may lead to an imbalanced production of pro-and antiinflammatory adipokines secreted from adipose tissue, which contributes to the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Low adiponectin levels are implicated in hepatic lipid accumulation and associated with NAFLD severity. 32 On the other hand, elevated adiponectin levels improve insulin sensitivity and enhance fatty acid oxidation, which in turn improve NAFLD pathology. 32 In addition, in one report, hepatic adiponectin signaling played a protective role against progression from simple steatosis to NASH in mice.…”
Section: Discussionmentioning
confidence: 99%
“…32 On the other hand, elevated adiponectin levels improve insulin sensitivity and enhance fatty acid oxidation, which in turn improve NAFLD pathology. 32 In addition, in one report, hepatic adiponectin signaling played a protective role against progression from simple steatosis to NASH in mice. 33 It is likely that the increased serum adiponectin level resulting from MVPA for !250 minÁwk 21 contributes to the improved pathophysiology of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, visceral fat plays a central role in the pathogenesis of insulin resistance and NAFLD owing to the fact that adipose tissue is not an inert tissue but it acts as a real active endocrine organ, thus furtherly impairing insulin resistance and influencing cytokine/adipokine pathways in terms of increased levels of FFA, adiponectin, leptin, TNF-α, IL-6. In particular adiponectin acts as a leading mediator in this pathogenetic events and its decreased levels are directly related to steatosis grade owing to the fact that adiponectin has a protective role decreasing lipid accumulation and fibrosis processes in liver [79] . Fatty free acids represent a well demonstred pathogenetic markers of insulin resistance and of its complications such as NAFLD owing to the fact that FFA cause liver cellular apoptosis and impair interplay between hepatic cells and immune system, cytokines, ROS and finally also impairing insulin production and signaling mechanisms [80][81][82][83][84][85][86] .…”
Section: Focus On Non Alcholic Fatty Liver Disease and Diabetesmentioning
confidence: 99%